2016
DOI: 10.1177/1087057115604141
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Intracellular Compound Concentration by RapidFire Mass Spectrometry Offers Insights into Cell Permeability

Abstract: One of the key challenges facing early stage drug discovery is understanding the commonly observed difference between the activity of compounds in biochemical assays and cellular assays. Traditionally, indirect or estimated cell permeability measurements such as estimations from logP or artificial membrane permeability are used to explain the differences. The missing link is a direct measurement of intracellular compound concentration in whole cells. This can, in some circumstances, be estimated from the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 13 publications
(23 reference statements)
1
50
0
4
Order By: Relevance
“…It was found that MB IAM values above 50 indicate promiscuous binding [57], and higher phospholipidotic potential [56][57][58][59] for discovery compound. It was also found that MB IAM showed a good correlation with the total cellular concentration of discovery compounds [60].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It was found that MB IAM values above 50 indicate promiscuous binding [57], and higher phospholipidotic potential [56][57][58][59] for discovery compound. It was also found that MB IAM showed a good correlation with the total cellular concentration of discovery compounds [60].…”
Section: Introductionmentioning
confidence: 86%
“…Recently, it was found that promiscuity (i.e., a discovery compound binding to multiple receptors) showed good correlation to the IAM MB of drug discovery compounds. The IAM MB data showed a good correlation with the intracellular concentration of compounds, indicating that membrane binding is important to get compounds into the cell [48]. Estimating the potential clinical dose as early as possible is an important aspect of the drug discovery process to help select the optimal compound profile and highest probability of successful progression to the clinic [49][50].…”
Section: Introductionmentioning
confidence: 99%
“…First, it relies on sensitive analytical MS for compound quantification, which is considered a low-throughput technology. However, we recently showed that extensions of our methodology can process >1,000 compounds per week (29,30), which should be sufficient for secondary screening of hits from biochemical assays. Second, for compounds that need to be activated in the cell (prodrugs), the F ic of the dosed parent molecule might not be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-based methodologies allow accurate determinations of intracellular drug concentrations using unlabeled compounds, but they are based on animal tissues and have low throughput (26,27). Therefore, we developed a cell-based methodology for determination of intracellular drug concentrations in a high-throughput format, which is applicable to a wide variety of cell systems, not only those directly relevant for the target pharmacology (28)(29)(30). Our method does not require chemical labeling, has a high sensitivity, and measures the unbound drug concentration.…”
mentioning
confidence: 99%
“…The coupling of a nano-LC system inline with a microfluidic chip to identify inhibitors of thrombin and factor Xa within complex mixtures of snake venom 8 623454J BXXXX10.1177/1087057115623454Journal of Biomolecular ScreeningWingfield and Wilson (2) demonstrates the versatility of MS and how it can be integrated with other assay platforms to deliver high-value data.…”
Section: From the Guest Editorsmentioning
confidence: 98%